Efectos diferenciales de la tasa de cambio real sobre el comercio internacional en Colombia (2017)
During the 2006-2013 period, Colombia experienced on the strongest appreciations in the world. During this same period, the volume of manufacturing exports fell nearly 50%, while the volume if imports rose in the same quantity. This work aims to determine the effect of the real exchange rate on the flow of international commerce in the manufacturing sector. For this end, and as a main approach, sub-sectoral real exchange rate indices are calculated for 19 manufacturing subsectors, noting the potential existence of heterogeneities between them. The price elasticities for exports and imports are also estimated using the bilateral and sub-sectoral real exchange rate index. The results indicate the existence of important differences between the behavior of the real exchange rate between subsectors, and that these differences explain the behavior of exports in the different manufacturing sectors, although the results are not so clear for the case of imports. These results suggest that policymakers should consider the differential effects of their policies on manufacturing performance when they affect the real exchange rate.